FLUIDOT: A Modular Microfluidic Platform for Single‐Cell Study and Retrieval, with Applications in Drug Tolerance Screening and Antibody Mining. Issue 3 (15th January 2023) - Breukers, Jolien; Ven, Karen; Struyfs, Caroline; Ampofo, Louanne; Rutten, Iene; Imbrechts, Maya; Pollet, Francesca; Van Lent, Julie; Kerstens, Winnie; Noppen, Sam; Schols, Dominique; De Munter, Paul; et al.
Abstract: Advancements in lab‐on‐a‐chip technologies have revolutionized the single‐cell analysis field. However, an accessible platform for in‐depth screening and specific retrieval of single cells, which moreover enables studying diverse cell types and performing various downstream analyses, is still lacking. As a solution, FLUIDOT is introduced, a versatile microfluidic platform incorporating customizable microwells, optical tweezers and an interchangeable cell‐retrieval system. Thanks to its smart microfluidic design, FLUIDOT is straightforward to fabricate and operate, rendering the technology widely accessible. The performance of FLUIDOT is validated and its versatility is subsequently demonstrated in two applications. First, drug tolerance in yeast cells is studied, resulting in the discovery of two treatment‐tolerant populations. Second, B cells from convalescent COVID‐19 patients are screened, leading to the discovery of highly affine, in vitro neutralizing monoclonal antibodies against SARS‐CoV‐2. Owing to its performance, flexibility, and accessibility, it is foreseen that FLUIDOT will enable phenotypic and genotypic analysis of diverse cell samples and thus elucidate unexplored biological questions. Abstract : FLUIDOT is a versatile microfluidic platform in which microwells, optical tweezers, and an interchangeable cell‐retrieval system are combined to enable in‐depth screening, specific retrieval, and various downstream analyses of single cells. FLUIDOT enables phenotypic and genotypic analysis of diverse cell types, as demonstrated in a drug tolerance study on yeast cells and a mAb discovery trajectory from human B cells.